Diseminasi Teknologi Budidaya Tanaman Wortel Ramah Lingkungan Di Dataran Rendah - Aluh Nikmatullah; Karwati Zanawi; Khaerul Muslim; Herman Suheru; Nurrachman; Rukmini Kusmarwiyah (Fakultas Pertanian Universitas Mataram, 2021)
The increasing demand for a good quality of carrot tubers has yet been achieved, partly due to limitation in cultivation area. Extension of cultivation to low land has been attempted and suitable cultivation technology with yields 17.5 – 25 ton/ha has been developed. However, cultivation of carrot in lowlands is very limited as farmers assume that carrots cannot be cultivated in the lowlands. To promote this, a community service (PKM) aimed to disseminate environmentally-friendly carrot cultivation technology in the lowlands has been undertaken in Bagik Polak Village, Labuapi District, West Lombok Regency from June to October 2020. The PKM was carried out in collaboration with the Gapoktan Bersatu and UPTD Agriculture of Labuapi District, through demonstration plots and extension. The activity began with socialization by discussion with the officials of Labuapi UPTD Agriculture and management of the Bersatu Gapoktan, followed by demplot for carrot cultivation at an altitude of ± 41 m above sea level. At harvest time, the demplot results were exposed to the community via extension at the house of the Gapoktan leader. By directly observing the demplot results, participants were motivated to cultivate environmentally-friendly carrots, and stated that they will undertake trials in theirs fields. The Labuapi UPTD will set a demplot in the UPTD yard and promote carrot plants in the program for yard optimality. In addition, the farmers agreed that this activity has bring a new inspiration to diversify vegetable crops with a higher economic crops